Wind of Change? Experimental Survey Evidence on the Covid-19 Shock and Socio-Political Attitudes in Europe - Gianmarco Daniele; Andrea F.M. Martinangeli; Francesco Passarelli; Willem Sas; Lisa Windsteiger (Center for Economic Studies and Ifo Institute (CESifo), 2020)
This paper investigates whether the Covid-19 crisis has affected the way we think about (political) institutions, as well as our broader (policy) attitudes and values. We fielded large online survey experiments in Italy, Spain, Germany and the Netherlands, well into the first wave of the epidemic (May-June), and included outcome questions on trust, voting intentions, policies & taxation, and identity & values. With a randomised survey ow we vary whether respondents are given Covid-19 priming questions first, before answering the outcome questions. With this treatment design we can also disentangle the health and economic effects of the crisis, as well as a potential “rally around the ag” component. We find that the crisis has brought about severe drops in interpersonal and institutional trust, as well as lower support for the EU and social welfare spending financed by taxes. This is largely due to economic insecurity, but also because of health concerns. A rallying effect around (scientific) expertise combined with populist policies losing ground forms the other side of this coin, and suggests a rising demand for competent leadership.
Keywords: D72; H51; H53; H55; O52; P52; 330; Covid-19; social trust; institutional trust; survey experiment; European Union; welfare; health; taxation; accountability; populism; values